Dari Eropa ke Nusantara: Filsafat Hukum bagi Modernisasi Hukum Islam - Kurniasih, Uun; Rizqa, Agitsna Alya; Khalimy , Akmad (Fakultas Hukum Universitas Primagraha, 2025)
The development of legal science has led scholars’ thoughts to form schools of legal theory, categorized according to their patterns of thought. The schools of thought of Sociological Jurisprudence and Sociology of Law seek to understand and explain the relationship between law and society. The study of Islamic law modernization discusses how Islamic law around the world evolves into a modern legal system capable of responding to contemporary challenges. This research aims to examine both schools of thought and analyze their implementation in the modernization of Islamic law in Indonesia. A qualitative method was used in this study with a library research approach. This study finds that the modernization of Islamic law in Indonesia is not merely a process of codification or textual reform but rather a complex social transformation. The school of Sociological Jurisprudence provides the understanding that law can function as a driver of change, while Sociology of Law emphasizes that any legal change can only be sustained if it aligns with the social realities of society. Both illustrate that the modernization of Islamic law proceeds through a dialectical process between the increasingly diverse needs of society and the normative values of Islam that form its foundation. These findings also indicate that Islamic law is not static but continuously adapts to the principles of justice, equality, and democracy that develop in the public sphere. The modernization of Islamic law in Indonesia is not merely an accommodation to the changing times but also a reflection of efforts to maintain the relevance of Islamic law so that it remains dynamic, applicable, and beneficial for contemporary society. This research contributes to the theoretical understanding of the relationship between law and society and provides practical guidance for policymakers and legal institutions in formulating regulations that are more relevant to the needs of today’s society.